Import content of Turkish production and exports: A sectoral analysis - Yasemin Erduman; Okan Eren; Selçuk Gül (Central Bank Review (CBR), 2020)
This study investigates the evolution of the import content of production and exports in Turkey for the 2002-2018 period. Based on 2002 and 2012 input-output tables and a large data set of production and foreign trade, we estimate the production and imported input use for 20 sectors, mainly from the manufacturing industry. We calculate import requirement ratios, comprising both direct and indirect effects, for each sector using the Leontief inverse matrix. Our findings indicate that import dependency increases for exports, but stays relatively stable for production over time. In general, the import content of production is lower than that of exports. This difference is mainly attributable to the services sector, which has low import dependency, yet a large share in production. Sectors with the highest import requirements are those with higher capital and technology intensity, such as petroleum products, basic metals, and motor vehicles. Agriculture, forestry and fishery; services and mining sectors have the lowest import requirements.
Keywords: C67; D57; F14; L60; 330; Import content; Import dependency; Input-output tables; Turkey